2011
DOI: 10.1063/1.3657137
|View full text |Cite
|
Sign up to set email alerts
|

Drive current and hot carrier reliability improvements of high-aspect-ratio n-channel fin-shaped field effect transistor with high-tensile contact etching stop layer

Abstract: A high-aspect-ratio 3D multi-gate n-channel fin-shaped field effect transistor (FinFET) has been integrated with a stressor of a highly tensile nitride film as the initial inter layer dielectric capping layer upon a (110)-orientated silicon-on-insulator wafer. Drastically enhanced electrical performances, such as 190% enhancement of peak channel mobility, 91% of peak transconductance, and 34% of saturation current, etc., are achieved for an NMOS FinFET with a gate length of 90 nm. The Ioff-Ion universal curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Another widely adopted concept is based in the deposition of a stressed film, typically Silicon Nitride (SiN) (also referred to as capping etch stopping layers (CESL)), over the transistor structure. [13][14][15][16][17] In this case, the strain in the channel results from mechanical interactions which depend on the geometry of the system and characteristics of the films. In contrast to Si x Ge 1-x and Si x C 1-x , for which the elastic behavior is well understood, our knowledge is limited on how amorphous SiN thin films behave in terms of developing stresses and mechanical properties, 18 particularly when featured over nanoscopic geometries of an intricate nature.…”
mentioning
confidence: 99%
“…Another widely adopted concept is based in the deposition of a stressed film, typically Silicon Nitride (SiN) (also referred to as capping etch stopping layers (CESL)), over the transistor structure. [13][14][15][16][17] In this case, the strain in the channel results from mechanical interactions which depend on the geometry of the system and characteristics of the films. In contrast to Si x Ge 1-x and Si x C 1-x , for which the elastic behavior is well understood, our knowledge is limited on how amorphous SiN thin films behave in terms of developing stresses and mechanical properties, 18 particularly when featured over nanoscopic geometries of an intricate nature.…”
mentioning
confidence: 99%
“…It has been reported that intrinsic stress in the deposited SiN films affects the performance of silicon metal-oxide-semiconductor fieldeffect transistors, 60,61 a-Si TFTs, 31 and InGaZnO TFTs. 62,63 Similarly, stress in the deposited SiN gate dielectrics may influence ZnO TFT characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…As the channel length of MOSFETs less than 1um, the hot-carrier damage becomes a serious reliability problem [1]. It reveals the degradation of device characteristics, life time and reliability of the device, so it is necessary to study and avoid the hot-carrier harmfulness of a MOSFET semiconductor device.…”
Section: Introductionmentioning
confidence: 99%